SARS-CoV-2 seroprevalence in healthcare workers at a frontline hospital in Tokyo - Hiroshi Fukuda (Nature Portfolio, 2021)
Abstract Healthcare workers (HCWs) are highly exposed to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. The actual coronavirus disease (COVID-19) situation, especially in regions that are less affected, has not yet been determined. This study aimed to assess the seroprevalence of SARS-CoV-2 in HCWs working in a frontline hospital in Tokyo, Japan. In this cross-sectional observational study, screening was performed on consented HCWs, including medical, nursing, and other workers, as part of a mandatory health checkup. The screening test results and clinical characteristics of the participants were recorded. The antibody seroprevalence rate among the 4147 participants screened between July 6 and August 21, 2020, was 0.34% (14/4147). There was no significant difference in the seroprevalence rate between frontline HCWs with a high exposure risk and HCWs working in other settings with a low exposure risk. Of those seropositive for SARS-CoV-2, 64% (9/14) were not aware of any symptoms and had not previously been diagnosed with COVID-19. In conclusion, this study provides insights into the extent of infection and immune status in HCWs in Japan, which has a relatively low prevalence of COVID-19. Our findings aid in formulating public health policies to control virus spread in regions with low-intensity COVID-19.